The importance of informal learning at work - Andries de Grip (IZA World of Labor, 2015)
Although early human capital theory recognized the relevance of workers' experience, its focus was on education and formal training. Recent studies find that much of the performance of newly hired workers is driven by learning by doing or learning from peers or supervisors in the workplace. Descriptive data show that workers learn a lot from the various tasks they perform on the job. Informal learning at work seems to be relevant for all age groups, although it drives more of the performance of younger workers. Informal learning is far more important for workers' human capital development than formal training courses.
Keywords: M53; J24; J22; 330; informal learning; human capital; learning by doing; knowledge spillovers; high performance workplace